2022
DOI: 10.3389/fnmol.2022.1078854
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of glycobiology-related genes in Parkinson’s disease brain

Abstract: The precise mechanisms initiating and perpetuating the cellular degeneration in Parkinson’s disease (PD) remain unclear. There is decreased expression of the main brain gangliosides, and GM1 ganglioside in particular, in the PD brain along with decreased expression of the genes coding for the glycosyltranferase and the sialyltransferase responsible for the synthesis of these brain gangliosides. However, potentially important pathogenic mechanisms contributing to the neurodegeneration in PD may also include alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 61 publications
0
8
1
Order By: Relevance
“…B4GALT1 is known to be linked to microglial activation and neuroinflammation. 35 In AD brains, elevated B4GALT1 expression correlated with heightened galactosylation of N-glycans. 36 Furthermore, a previous study indicated a notable increase in B4GALT1 gene expression within the substantia nigra of PD patients compared to controls.…”
Section: Discussionmentioning
confidence: 94%
“…B4GALT1 is known to be linked to microglial activation and neuroinflammation. 35 In AD brains, elevated B4GALT1 expression correlated with heightened galactosylation of N-glycans. 36 Furthermore, a previous study indicated a notable increase in B4GALT1 gene expression within the substantia nigra of PD patients compared to controls.…”
Section: Discussionmentioning
confidence: 94%
“…Glycosyltransferases are enzymes that catalyze the transfer of sugar molecules, resulting in the synthesis of saccharides and glycoconjugates. Aberrant gene expression levels of glycosyltransferases have been implicated in multiple neurodegenerative diseases including Alzheimer’s disease, Parkinson’s disease, and Amyloid Lateral Sclerosis (ALS) (Moll et al 2020; Schneider and Singh 2022). Consequently, it may be interesting to query the expression levels of the glycotransferase gene family in brain tissue compared to other regions of the body.…”
Section: Resultsmentioning
confidence: 99%
“…Glycosylation is an abundant post-translational modification (PTM), particularly on membrane-bound and lysosomal proteins, and its dysregulation has also been found in PD brains (Schneider and Singh, 2022). In addition to protein synthesis, the ER also regulates glycosylation and functionalization of proteins.…”
Section: Interaction Between Er Stress and Other Pd Pathological Eventsmentioning
confidence: 99%
“…In addition to protein synthesis, the ER also regulates glycosylation and functionalization of proteins. Abnormal glycosylation is known to lead to abnormal protein deposition, causing ER overload and triggering ER stress (Schneider and Singh, 2022).…”
Section: Interaction Between Er Stress and Other Pd Pathological Eventsmentioning
confidence: 99%